Time budgets of breeding Mallard in northern Sweden - Asplund, Cay (Wildfowl, 1981)
Time spent in different activities by breeding Mallard Anas platyrhynchos was studied in two restored lakes in northern Sweden. As soon as females arrived, egg-laying started. Aggression between pairs consumed less than 0.5% of time during the laying and ceased during incubation. Females spent more time in feeding than males during laying and incubation. Prior to moulting, males began to spend more time in feeding. Flocks of males were first observed on 25 May. These flocks disturbed the feeding females. Female Mallard in northern breeding areas does not have much time for building up metabolic reserves before laying. During incubation phase they exploit the whole day and the drastically increased food supply.